Recent peat and carbon accumulation following the Little Ice Age in northwestern Quebec, Canada - Piilo, Sanna; Zhang, Hui; Garneau, Michelle; Gallego-Sala, Angela V.; Amesbury, Matthew; Väliranta, Minna (Environmental Research Letters, 2019)
Peatland ecosystems are important carbon sinks, but also release carbon back to the atmosphere as carbon dioxide and methane. Peatlands therefore play an essential role in the global carbon cycle. However, the response of high-latitude peatlands to ongoing climate change is still not fully understood. In this study, we used plant macrofossils and peat property analyses as proxies to document changes in vegetation and peat and carbon accumulation after the Little Ice Age. Results from 12 peat monoliths collected in high-boreal and low-subarctic regions in northwestern Quebec, Canada, suggest high carbon accumulation rates for the recent past (post AD 1970s). Successional changes in plant assemblages were asynchronous within the cores in the southernmost region, but more consistent in the northern region. Average apparent recent carbon accumulation rates varied between 50.7 and 149.1 g C m(-2) yr(-1) with the northernmost study region showing higher values. The variation in vegetation records and peat properties found within samples taken from the same sites and amongst cores taken from different regions highlights the need to investigate multiple records from each peatland, but also from different peatlands within one region. Peer reviewed